PERAN MASYARAKAT LOKAL DALAM PENGELOLAAN DAYA TARIK WISATA SPIRITUAL PURA PUNCAK BUKIT SINUNGGAL KABUPATEN BULELENG (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2025)
Puncak Bukit Sinunggal Temple is one of the temples located in Tajun Village, Kubutambahan District, Buleleng Regency, North Bali. This temple is located on a hill known as Bukit Tunggal, offering beautiful scenery and a distinctive spiritual atmosphere. As one of the dang kahyangan temples, Pura Bukit Sinunggal has a unique and historical value that attracts tourists, especially those seeking a spiritual tourism experience. This study aims to determine the role of local communities in the management of spiritual tourism attractions at Puncak Bukit Sinunggal Temple. The method used is qualitative research with a case study approach, involving data collection through observation, interviews, documentation, and literature study. This study aims to determine the role of local communities in the management of spiritual tourism attractions at Puncak Bukit Sinunggal Temple. The method used is qualitative research with a case study approach, involving data collection through observation, interviews, documentation, and literature study. The results showed that Puncak Bukit Sinunggal Temple offers various attractions, such as prayeractivities, natural beauty, unique historical buildings, and meditation places. Available facilities include parking areas, toilets, wantilan, and food stalls that support visitor comfort. From the environmental aspect, the local community together with the temple management routinely carry out mutual cooperation and cleaning of the temple area to maintain the cleanliness and sustainability of this sacred place. In the planning aspect, it is recommended to add a gazebo on the stairs leading to the temple and widen the stairs to facilitate access. The organization of management is carried out by the local traditional village, while supervision is carried out by pecalang and the temple management to maintain order and security.
Keywords: Community Role; Management; Spiritual Tourism Attraction; Puncak Temple Bukit Sinunggal